Understanding the Islamic Viewpoint on Religious Pluralism in Nigeria with Special Reference to Ahl Al-Kitab - Rabiu, Aliyu Alhaji; Modibbo, Yakubu (IIUM Journal of Religion and Civilisational Studies, 2018)
Islam, as a universal religion and a complete way of life, acknowledges the existence of other religions just as it does to the diversity of human nature. This paper focuses on the Jews and the Christians, referred to as Ahl al-Kitab, who are given special recognition in the Qur’an, which is God’s final revelation to humanity. Islam, therefore, allows for Muslims to interact with the followers of other religions, especially the peace-loving and non-hostile non-Muslims. Despite this permission, there are often hostile relationships between Muslims, Christians, and adherents of other religious traditions in some parts of the world, including Nigeria; this hostility often leads to violence that may be fuelled by political, tribal, or regional undertones. Over time, this trend has led to the loss of lives and the destruction of invaluable properties and places of worship across multicultural and multi-religious communities. Observably, ignorance and misconceptions by the adherents of the two major religions play a considerable role in virtually all the politico-religious crises and communal-tribal clashes that have occurred in Nigeria since the late 1970s, thereby challenging the peaceful coexistence and national development of the nation. This paper unveils the Islamic viewpoint on religious pluralism and the unmatchable position afforded to the Ahl Al-Kitab by Islam with the aim of fostering an understanding among the people for better interfaith relations and national development. The researchers recommend that the government use all possible means to check the excesses of individuals and groups against the manipulation of religion to cause unrest, and that religious bodies use dialogue as a viable tool to foster understanding. This paper uses exegetical and descriptive methods of research.